Design of epitope based vaccine against shrimp white spot syndrome virus (WSSV) by targeting the envelope proteins: An immunoinformatic approach - Momtaz, F.; Foysal, J.; Rahman, M.; Fotedar, Ravi (2019)
The shrimp white spot syndrome virus (WSSV) causes significant damage to aquaculture production worldwide but a vaccine, eliciting the immunogenicity of shrimps against WSSV has yet to be developed. Thus, a programmed immunoinformatics study was conducted to find out the potential immunogens based on genome-wide screening of WSSV envelope proteins. The measurements of the phylogenetic and evolutionary distances found the common geographical routes of three countries, where the proteins from other six countries were clustered together. Among all the four major envelope proteins i.e., VP19, VP24, VP26, and VP28; AAO69663.1 from VP26 showed the highest antigenicity and thus selected for further studies. The properties of the secondary and tertiary structure including the modelled 3D protein revealed that the protein had all the properties required for a protective immunogen. The peptide regions ranging from 99 to 115 and 98 to 106, representing the sequences “VTAPRTDPAGTGAENSN” and “TVTAPRTDP” were found to be most effective regions for B-cell linear and cytotoxic T lymphocyte (CTL), respectively. The CTL epitope also showed a strong and stable interaction with the MHC class I and class II molecules, reported to be found in fish. Therefore, the present epitope could be used as a potential vaccine candidate against WSSV.